The Effect of Consuming Eggs and Iron Tablets on Increasing Hb Levels in Adolescent Girls at the Aisyiyah Orphanage in Klaten - Kuswati, Kuswati; Yulaikah, Siti (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2025)
Background: Anemia is a common problem among teenagers. Anemia control in adolescent girls and women of childbearing age (WUS) by providing Fe tablets..Eggs are one of the foods that contain iron and can be a substitute for Fe tablets.Objective : This study aims to determine the effect of consuming Fe tablets, eggs, and Fe tablets combined with eggs on increasing hemoglobin levels in adolescent girls at the Aisyah Klaten Orphanage.Methods: This study was conducted with a quantitative approach using a quasi-experimental design with a pretest-posttest control group design. The location of the study was at the Aisyiah Klaten Orphanage. The research was conducted from January to July 2024. The population in the study were all adolescent girls at the orphanage in Aisyiyah Klaten. The sampling technique was Total Sampling of 45 respondents divided into 15 samples each. The research instruments were Hb meter laboratory examination tools (Easy Touch GCHb) and observation sheets. Analysis of research data using the Paired t-test and Independent t-test.Results: There was an effect after consuming Fe tablets (p = 0.0003), eggs (p = 0.0099), and Fe tablets combined with eggs (p = 0.0016) on increasing Hb levels in adolescent girls. The average increase in hemoglobin levels after consuming Fe tablets was 1.05 g/dl, egg consumption was 0.98 g/dl, and consumption of Fe tablets combined with eggs was 0.93 g/dl.Conclusion: Consumption of Fe tablets, eggs, and Fe tablets combined with eggs affected the increase in Hb levels in female adolescents at the Aisyah Klaten orphanage. The comparison of the average increase in Hb levels after consuming Fe tablets was higher than consuming eggs or Fe tablets combined with eggs.